Effect Of Jicama Flour Substitution On Sensoris, Physical, And Chemical Characteristic Of Gluten-Free Soft Cookies - Adila Khairunisa; Pudji Astuti (Jurnal Pendidikan Tata Boga dan Teknologi, 2026)
The increasing dependence on wheat flour has encouraged the development of gluten-free food products based on local ingredients. This study aimed to analyze the effect of jicama flour substitution on the sensory, physical, and chemical characteristics of mocaf-based gluten-free soft cookies and to determine the most appropriate substitution level. A quantitative experimental method with a single-factor design was employed using four substitution levels: F0 (100% mocaf flour), F1 (80% mocaf flour : 20% jicama flour), F2 (60% mocaf flour : 40% jicama flour), and F3 (40% mocaf flour : 60% jicama flour). The observed parameters included sensory acceptance, color and texture characteristics, moisture content, and protein content. Data were analyzed using the Kruskal–Wallis test followed by the Mann–Whitney test. The results showed that jicama flour substitution significantly affected the characteristics of soft cookies (p < 0.05). Formulation F2 achieved the highest sensory scores for taste (8.17), texture (8.10), and overall acceptance (8.17). Moisture content ranged from 14.36% to 15.66%, while protein content ranged from 1.59% to 3.70%. Although protein content increased with increasing levels of jicama flour substitution, the moisture content of all formulations exceeded the Indonesian National Standard (SNI) requirement for cookies. Based on the sensory, physical, and chemical evaluations, formulation F2 exhibited favorable characteristics and was well accepted as a mocaf-based gluten-free soft cookie..